Evaluation of butorphanol-azaperone-medetomidine in captive cheetah (Acinonyx jubatus) immobilization. (January 2019) - Semjonov, Aleksandr; Raath, Jacobus P.; Laubscher, Liesel; Orro, Toomas; Pfitzer, Silke; Tiirats, Toomas; Rogers, Peter Stewart; Andrianov, Vladimir
Abstract: Objective: The butorphanol-azaperone-medetomidine fixed-dose combination (BAM, respectively, 30-12-12 mg mL −1 ) with subsequent antagonism by naltrexone-atipamezole was evaluated for reversible immobilization of captive cheetahs ( Acinonyx jubatus ). Study design: Prospective, clinical trial. Animals: Twelve cheetahs (six males and six females, weighing 37–57 kg) housed in enclosures, were immobilized at Hoedspruit Endangered Species Centre in the Republic of South Africa. Methods: BAM volume dose rate was 0.009–0.014 mL kg −1 (mean ± standard deviation 0.010 ± 0.001 mL kg −1 ). Total dose in all animals was 0.5 mL. The actual doses were as follows: butorphanol (0.29 ± 0.04 mg kg −1 ), azaperone (0.12 ± 0.01 mg kg −1 ) and medetomidine (0.12 ± 0.01 mg kg −1 ). Physiologic variables and quality of immobilization were recorded every 5 minutes beginning at 15–20 minutes after darting. Arterial blood samples were collected three times at 20, 30 and 40 minutes after darting from all animals for analysis of blood oxygenation and acid-base status. Results: The inductions were calm and smooth and mean induction time was 4.0 ± 1.1 minutes. Heart rate (50 ± 9 beats minute −1 ) and respiratory frequency (20 ± 3 breaths minute −1 ) were stable throughout immobilization. The recovery time after reversing with naltrexone and atipamezole was 9.1 ± 3.6 minutes. Conclusions: and clinical relevance BAM proved to be a reliable and cardiovascular stable drug combination for immobilization of cheetahs.